2021
DOI: 10.1039/d1cp00181g
|View full text |Cite
|
Sign up to set email alerts
|

Protein flexibility reduces solvent-mediated friction barriers of ligand binding to a hydrophobic surface patch

Abstract: Solvent fluctuations have been explored in detail for idealized and rigid hydrophobic model systems, but so far it has remained unclear how internal protein motions and their coupling to the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
2
2
0
Order By: Relevance
“… 46 , 47 A recent study of binding of a model ligand to a hydrophobic surface patch of ubiquitin showed that protein flexibility modulates the density fluctuations, and hence the compressibility, of the surrounding hydration layers in such a way that partial dewetting of the binding interface is facilitated and the friction associated with the binding process is reduced. 48 These results agree with a recent study, which showed that forces associated with joint protein–water motions lower the friction along the reaction coordinate for different biomolecular processes, such as Fe-CO bond rupture in myoglobin, unfolding of a small protein domain, and dissociation of an insulin dimer. 49 Furthermore, by studying fluctuations of the local water density near protein surfaces and the dewetting of surface patches, Rego et al established a classification of surface hydrophobicity that is independent of the chemical nature of the constituent atoms.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“… 46 , 47 A recent study of binding of a model ligand to a hydrophobic surface patch of ubiquitin showed that protein flexibility modulates the density fluctuations, and hence the compressibility, of the surrounding hydration layers in such a way that partial dewetting of the binding interface is facilitated and the friction associated with the binding process is reduced. 48 These results agree with a recent study, which showed that forces associated with joint protein–water motions lower the friction along the reaction coordinate for different biomolecular processes, such as Fe-CO bond rupture in myoglobin, unfolding of a small protein domain, and dissociation of an insulin dimer. 49 Furthermore, by studying fluctuations of the local water density near protein surfaces and the dewetting of surface patches, Rego et al established a classification of surface hydrophobicity that is independent of the chemical nature of the constituent atoms.…”
Section: Introductionsupporting
confidence: 92%
“…Such an approach might be suitableand to some extent unavoidable, given the limitations set by the requirement for a 3D grid. However, fluctuations in the hydration layers are coupled to protein motions and, thus, can be affected by the restraints. , A recent study of binding of a model ligand to a hydrophobic surface patch of ubiquitin showed that protein flexibility modulates the density fluctuations, and hence the compressibility, of the surrounding hydration layers in such a way that partial dewetting of the binding interface is facilitated and the friction associated with the binding process is reduced . These results agree with a recent study, which showed that forces associated with joint protein–water motions lower the friction along the reaction coordinate for different biomolecular processes, such as Fe-CO bond rupture in myoglobin, unfolding of a small protein domain, and dissociation of an insulin dimer .…”
Section: Introductionsupporting
confidence: 87%
“…Intrinsically disordered proteins (IDPs) and intrinsically disordered regions (IDRs) of otherwise structured proteins are ubiquitous and involved in many signaling and regulatory processes. Interactions between proteins and water and the dynamics of water around proteins play key roles in protein function, including enzyme activity and allostery, , and while these properties have been extensively studied for structured proteins, less is known for IDPs and proteins with IDRs. Some studies indicate more restricted dynamics of water around IDRs and IDPs compared to structured systems of similar size, the origin of which appears to be due at least in large part to a greater presence of charged groups in disordered regions .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we analyzed the dynamics of water molecules in the protein hydration layer (PHL), as they are coupled to protein dynamics. [56][57][58][59][60][61][62][63] To investigate the effect of the altered protein dynamics in the crowded environment of the condensate on the hydration water dynamics, the reorientation motions (rotations) of the water molecules in the PHL were probed, which was defined as the region within 0.5 nm of the protein surface. To quantify the water reorientation motions in the PHL, we computed the time ACFs of the dipole moment vector of each water molecule (Eq.…”
mentioning
confidence: 99%